Secondary battery and electronic device

By adding sulfur-oxygen double bond compounds and nitrile compounds to the electrolyte of lithium-ion batteries, and controlling their content and the thickness of the positive electrode material layer, the problem of abnormal charge and discharge capacity ratio during the cycle of lithium-ion batteries is solved, and better cycle performance and energy density are achieved.

CN119725735APending Publication Date: 2025-03-28DONGGUAN AMPEREX TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311281928.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The charging and discharging capacity ratio of lithium-ion batteries during circulation is abnormal, resulting in excessive capacity loss or excessive self-discharge.

Method used

By adding sulfur-oxygen double bond compounds and nitrile compounds to the electrolyte, and controlling their mass ratio and total mass percentage content, as well as the thickness of the positive electrode material layer, a stable positive electrode electrolyte interface film is formed and side reactions are reduced.

Benefits of technology

The circulation performance of lithium-ion batteries is improved, the abnormality of the charge and discharge capacity ratio is reduced, and the energy density and cycle life of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004480919660000031
    Figure BDA0004480919660000031
  • Figure BDA0004480919660000032
    Figure BDA0004480919660000032
  • Figure BDA0004480919660000041
    Figure BDA0004480919660000041
Patent Text Reader

Abstract

The invention provides a secondary battery and an electronic device, the secondary battery comprises a positive pole piece and an electrolyte, the electrolyte comprises a sulfur-oxygen double-bond compound and a nitrile compound, based on the total mass of the electrolyte, the mass percentage content of the sulfur-oxygen double-bond compound is A1%, the mass percentage content of the nitrile compound is A2%, and 0.08 < = A1 / A2 < = 2.15; the sum of the mass percentages of the sulfur-oxygen double-bond compound and the nitrile compound is A%, and A is greater than or equal to 3 and less than or equal to 15; the positive pole piece comprises a positive pole material layer, the thickness of the positive pole material layer is D [mu] m, and A / D is larger than or equal to 0.08 and smaller than or equal to 0.42. The electrolyte comprises a sulfur-oxygen double-bond compound and a nitrile compound, and the mass ratio and the mass sum of the sulfur-oxygen double-bond compound and the nitrile compound and the ratio of the mass sum of the sulfur-oxygen double-bond compound and the nitrile compound to the thickness of the positive electrode material layer are within the range of the application. The problem that the charge-discharge capacity ratio is abnormal in the circulation process can be solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrochemical technology, and in particular to a secondary battery and an electronic device. Background Art

[0002] Secondary batteries (such as lithium-ion batteries) are widely used in smart phones, wearable devices, consumer drones, electric vehicles and other fields due to their high energy density, long cycle life and no memory effect. With the widespread application of lithium-ion batteries in the above fields, the market has higher and higher requirements for the energy density of lithium-ion batteries.

[0003] As energy density increases, the voltage of lithium-ion batteries also increases. The increase in lithium-ion battery voltage will affect the positive electrode material layer, intensify the side reactions between the electrolyte and the positive electrode, and the generated soluble byproducts, gases, and transition metal ions dissolved from the positive electrode will shuttle to the negative electrode. At the same time, the soluble byproducts and gases generated by the negative electrode will also shuttle to the positive electrode for oxidation, resulting in an abnormal charge-discharge capacity ratio (C / D) during the cycle of the lithium-ion battery. Summary of the invention

[0004] The purpose of this application is to provide a secondary battery and an electronic device to improve the problem of abnormal charge-discharge capacity ratio during the cycle of the secondary battery. The specific technical solution is as follows:

[0005] The first aspect of the present application provides a secondary battery, which includes a positive electrode plate, a negative electrode plate, a separator and an electrolyte, wherein the electrolyte includes a sulfur-oxygen double bond compound and a nitrile compound, based on the total mass of the electrolyte, the mass percentage of the sulfur-oxygen double bond compound is A1%, the mass percentage of the nitrile compound is A2%, 0.08≤A1 / A2≤2.15; the sum of the mass percentages of the sulfur-oxygen double bond compound and the nitrile compound is A%, 3≤A≤15; the positive electrode plate includes a positive electrode current collector and a positive electrode material layer disposed on at least one surface of the positive electrode current collector, the thickness of the positive electrode material layer is Dμm, 0.08≤A / D≤0.42. By regulating the electrolyte including the sulfur-oxygen double bond compound and the nitrile compound, the mass ratio of the sulfur-oxygen double bond compound and the nitrile compound, and the sum of the masses, and the ratio of the sum of the masses of the sulfur-oxygen double bond compound and the nitrile compound to the thickness of the positive electrode material layer within the scope of the present application, the problem of abnormal charge and discharge capacity ratio during the cycle of the secondary battery can be improved.

[0006] In one embodiment of the present application, the secondary battery satisfies at least one of the following characteristics: (1) 0.142≤A / D≤0.42; (2) 0.5≤A1≤5.2, 2.4≤A2≤8.1; (3) 15≤D≤60. The secondary battery has the above characteristics, which is conducive to further improving the problem of abnormal charge and discharge capacity ratio during the cycle of the secondary battery. In addition, it can also enable the secondary battery to have a higher energy density while taking into account good cycle performance.

[0007] In one embodiment of the present application, the sulfur-oxygen double bond compound includes 1,3-propane sultone, vinyl sulfate, propene sultone, 3-fluoro-1,3-propane sultone, 1,2-propane sultone, 1,4-butane sultone, 2,4-butane sultone or At least one of. The nitrile compound includes at least one of malononitrile, succinonitrile, glutaronitrile, adiponitrile, heptane dinitrile, octanedinitrile, 3,3'-oxydipropionitrile, hexane-2-enedinitrile, trans-butylenedinitrile, 2-pentene dinitrile, methyl glutaronitrile, 4-cyano heptane dinitrile, (Z)-but-2-enedinitrile, 2,2,3,3-tetrafluorosuccinonitrile, ethylene glycol bis(propionitrile) ether, 1,3,6-hexanetrinitrile, 1,3,5-pentanetricarbonitrile, 4-(2-cyanoethyl) heptane dinitrile or 1,2,3-tris(2-cyanoethoxy)propane. By selecting the above-mentioned sulfur-oxygen double bond compound, a relatively stable positive electrode electrolyte interface film can be formed on the surface of the positive electrode material layer, thereby improving the problem of abnormal charge and discharge capacity ratio during the cycle of the secondary battery. By selecting the above-mentioned nitrile compounds, the nitrile compounds can be adsorbed on the positive electrode surface to cover the positive electrode active sites, reduce the side reactions of the positive electrode electrolyte and the positive electrode material layer, and thus improve the problem of abnormal charge and discharge capacity ratio during the cycle of the secondary battery.

[0008] In one embodiment of the present application, the electrolyte satisfies at least one of the following characteristics: (1) the sulfur-oxygen double bond compound includes at least one of 1,3-propane sultone or vinyl sulfate, and the electrolyte also includes adiponitrile, succinonitrile and 1,3,6-hexanetrinitrile; (2) the sulfur-oxygen double bond compound includes at least one of 1,3-propane sultone or vinyl sulfate, and the electrolyte also includes adiponitrile and ethylene glycol bis(propionitrile) ether. The secondary battery has the above characteristics, which is conducive to further improving the problem of abnormal charge and discharge capacity ratio during the cycle of the secondary battery.

[0009] In one embodiment of the present application, the electrolyte further includes fluoroethylene carbonate (FEC), and the mass percentage of the fluoroethylene carbonate is A3% based on the total mass of the electrolyte, 1.8≤A3≤9.8. By regulating the electrolyte to also include FEC and the mass percentage of FEC within the scope of the present application, FEC can form a relatively stable solid electrolyte interface film on the surface of the negative electrode material layer, reduce the amount of side reaction products on the negative electrode side, and the synergistic protection of the positive electrode and the negative electrode can reduce the shuttling process of the side reaction products on the positive electrode side to the negative electrode and the shuttling process of the side reaction products on the negative electrode side to the positive electrode, thereby improving the problem of abnormal charge and discharge capacity ratio during the cycle of the secondary battery.

[0010] In one embodiment of the present application, 0.5≤A / A3≤5.2. By adjusting the value of A / A3 within the scope of the present application, it is helpful to form a relatively complete positive electrode electrolyte interface film with a suitable thickness on the surface of the positive electrode material layer, and at the same time form a relatively complete solid electrolyte interface film with a suitable thickness on the surface of the negative electrode material layer, thereby improving the problem of abnormal charge and discharge capacity ratio during the cycle of the secondary battery.

[0011] In one embodiment of the present application, the electrolyte further comprises a compound of formula (I):

[0012]

[0013] wherein X is selected from CR6 or N; R1, R2 and R3 are each independently selected from a hydrogen atom, a halogen, a C2-C5 carbonyl group, a C1-C5 aldehyde group, a C1-C5 alkyl group which is unsubstituted or substituted by Ra, a C2-C5 alkenyl group which is unsubstituted or substituted by Ra, an alkynyl group which is unsubstituted or substituted by Ra, a C3-C5 N-heterocycloalkyl group which is unsubstituted or substituted by Ra, a C3-C5 N-heteroaryl group; R4, R5 and R6 are each independently selected from a hydrogen atom, a C1-C5 alkylthio group, a C2-C5 thioether group, a C3-C5 N-heterocycloalkane group, a C3-C5 N-heteroaryl group, C3-C5 N heteroaryl, C1-C5 alkyl which is unsubstituted or substituted by Ra, C2-C5 alkenyl which is unsubstituted or substituted by Ra, C2-C5 alkynyl which is unsubstituted or substituted by Ra; the substituent Ra of each group is independently selected from halogen, C1-C5 aldehyde group, C2-C5 carbonyl group, C2-C5 ester group, sulfonic acid group, amino group, C2-C5 amide group or cyano group; based on the total mass of the electrolyte, the mass percentage of the compound of formula (I) is A4%, 0.01≤A4≤5, preferably 0.1≤A4≤3. By regulating the electrolyte to also include the compound of formula (I), the type and content of the compound of formula (I) within the scope of this application, it is helpful to form a positive electrode electrolyte interface film with good ion diffusion performance and relatively stable on the surface of the positive electrode material layer, thereby improving the problem of abnormal charge and discharge capacity ratio during the cycle of the secondary battery.

[0014] In one embodiment of the present application, the compound of formula (I) is selected from at least one of the following compounds:

[0015]

[0016]

[0017] By selecting the compound of formula (I), a relatively stable positive electrode electrolyte interface film with good ion diffusion performance can be formed on the surface of the positive electrode material layer, thereby improving the problem of abnormal charge and discharge capacity ratio during the cycle of the secondary battery.

[0018] In one embodiment of the present application, the positive electrode material layer includes a positive electrode active material, the particle size Dv10 of the positive electrode active material is D1 μm, the particle size Dv50 of the positive electrode active material is D2 μm, 2.4≤D1≤5.5, 1.5≤D2 / D1≤5. By regulating the values ​​of D1 and D2 / D1 within the scope of the present application, the positive electrode active material can have a suitable particle size, and the side reactions of the positive electrode side electrolyte and the positive electrode material layer can be reduced, thereby reducing the generation of side reaction products on the positive electrode side, thereby improving the problem of abnormal charge and discharge capacity ratio during the cycle of the secondary battery.

[0019] In one embodiment of the present application, 4.8≤A×(D2 / D1)≤55, preferably 10≤A×(D2 / D1)≤50. By adjusting the value of A×(D2 / D1) within the scope of the present application, the sum of the mass percentages of the sulfur-oxygen double bond compound and the nitrile compound matches the particle size of the positive electrode active material, and the side reactions of the positive electrode electrolyte and the positive electrode material layer are reduced, and the amount of side reaction products on the positive electrode side is reduced, thereby improving the problem of abnormal charge and discharge capacity ratio during the cycle of the secondary battery.

[0020] In one embodiment of the present application, the average sphericity of the positive electrode active material is S50, 0.65≤S50≤0.99. By regulating the value of S50 within the scope of the present application, it is helpful to reduce the pressure between the positive electrode active material particles in the positive electrode material layer during cold pressing, reduce the degree of crushing of the positive electrode active material particles, reduce the occurrence of side reactions of the positive electrode side electrolyte and the positive electrode material layer, and reduce the amount of side reaction products on the positive electrode side, thereby improving the problem of abnormal charge and discharge capacity ratio during the cycle of the secondary battery.

[0021] The second aspect of the present application provides an electronic device, which includes the secondary battery in any of the above embodiments. Therefore, the electronic device provided by the present application has good performance.

[0022] Beneficial effects of this application:

[0023] The present application provides a secondary battery and an electronic device, wherein the secondary battery comprises a positive electrode plate, a negative electrode plate, a separator and an electrolyte, wherein the electrolyte comprises a sulfur-oxygen double bond compound and a nitrile compound, wherein the mass percentage of the sulfur-oxygen double bond compound is A1%, the mass percentage of the nitrile compound is A2%, and 0.08≤A1 / A2≤2.15 based on the total mass of the electrolyte; the sum of the mass percentages of the sulfur-oxygen double bond compound and the nitrile compound is A%, and 3≤A≤15; and the positive electrode plate comprises a positive electrode current collector and a positive electrode material layer disposed on at least one surface of the positive electrode current collector, wherein the thickness of the positive electrode material layer is Dμm, and 0.08≤A / D≤0.42. By regulating the electrolyte comprising the sulfur-oxygen double bond compound and the nitrile compound, the mass ratio of the sulfur-oxygen double bond compound and the nitrile compound, and the sum of the masses, and the ratio of the sum of the masses of the sulfur-oxygen double bond compound and the nitrile compound to the thickness of the positive electrode material layer within the scope of the present application, the problem of abnormal charge and discharge capacity ratio during the cycle of the secondary battery can be improved.

[0024] Of course, implementing any product or method of the present application does not necessarily require achieving all of the advantages described above at the same time. DETAILED DESCRIPTION

[0025] The technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application.

[0026] It should be noted that in the following content, lithium-ion batteries are used as an example of secondary batteries to explain the present application, but the secondary batteries of the present application are not limited to lithium-ion batteries. The specific technical solution is as follows:

[0027] The present application provides a secondary battery, which includes a positive electrode plate, a negative electrode plate, a separator and an electrolyte, wherein the electrolyte includes a sulfur-oxygen double bond compound and a nitrile compound, based on the total mass of the electrolyte, the mass percentage of the sulfur-oxygen double bond compound is A1%, the mass percentage of the nitrile compound is A2%, 0.08≤A1 / A2≤2.15, illustratively, A1 / A2 can be 0.08, 0.1, 0.2, 0.4, 0.6, 0.8, 1, 1.2, 1.4, 1.6, 1.8, 2, 2.1, 2.15 or a range consisting of any two of the above values. The sum of the mass percentages of the sulfur-oxygen double bond compound and the nitrile compound is A%, 3≤A≤15, illustratively, A can be 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15 or a range consisting of any two of the above values. The positive electrode sheet includes a positive electrode current collector and a positive electrode material layer disposed on at least one surface of the positive electrode current collector, the thickness of the positive electrode material layer is Dμm, 0.08≤A / D≤0.42, preferably 0.142≤A / D≤0.42. Exemplarily, A / D can be 0.08, 0.1, 0.13, 0.142, 0.15, 0.17, 0.2, 0.23, 0.25, 0.27, 0.3, 0.33, 0.35, 0.37, 0.4, 0.42 or a range consisting of any two of the above values. The negative electrode sheet includes a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector.

[0028] The inventors have found that the electrolyte includes sulfur-oxygen double bond compounds and nitrile compounds. The nitrile compounds are adsorbed on the surface of the positive electrode to cover the positive electrode active sites. The sulfur-oxygen double bond compounds form a relatively stable positive electrode electrolyte interface film on the surface of the positive electrode material layer. The two are used together to synergistically reduce the side reactions of the electrolyte and the positive electrode material layer on the positive electrode side. By regulating the ratio of the sum of the mass percentages of the sulfur-oxygen double bond compounds and the nitrile compounds to the thickness of the positive electrode material layer, the positive electrode active sites can be effectively covered and a positive electrode electrolyte interface film of appropriate thickness can be formed, which can reduce the amount of side reaction products generated on the positive electrode side and the amount of transition metal ions dissolved, reduce the risk of shuttle-type self-discharge and self-discharge caused by transition metal microdendrites, and thus improve the problem of abnormal charge and discharge capacity ratio during the cycle of the secondary battery. Thus, by regulating the electrolyte including the sulfur-oxygen double bond compound and the nitrile compound, the mass ratio and the mass sum of the sulfur-oxygen double bond compound and the nitrile compound, and the ratio of the mass sum of the sulfur-oxygen double bond compound and the nitrile compound to the thickness of the positive electrode material layer within the scope of this application, the problem of abnormal charge and discharge capacity ratio during the cycle of the secondary battery can be improved. In this application, the maximum value of C / D in the cycle of the secondary battery (C / D) maxAs an indicator for evaluating the C / D of lithium-ion batteries, the abnormal charge-discharge capacity ratio during the cycle of secondary batteries refers to excessive capacity loss or excessive self-discharge during the cycle. Specifically, (C / D) max ≥1.05 is judged as abnormal charge-discharge capacity ratio during the cycle of the secondary battery.

[0029] In one embodiment of the present application, 0.5≤A1≤5.2, 2.4≤A2≤8.1. For example, A1 can be 0.5, 1, 1.4, 1.6, 1.8, 2, 2.2, 2.4, 2.6, 2.8, 3, 3.2, 3.4, 3.6, 3.8, 4, 4.2, 4.4, 4.6, 4.8, 5, 5.2, or a range consisting of any two of the above values; A2 can be 2.4, 2.8, 3, 3.4, 3.8, 4, 4.4, 4.8, 5, 5.4, 5.8, 6, 6.4, 6.8, 7, 7.4, 7.8, 8, 8.1, or a range consisting of any two of the above values. By regulating the values ​​of A1 and A2 within the scope of the present application, it is helpful to form an effective positive electrode electrolyte interface film on the surface of the positive electrode material layer, and the amount of side reaction products on the positive electrode side is moderate and the thickness of the formed positive electrode electrolyte interface film is moderate, which is beneficial to improve the problem of abnormal charge and discharge capacity ratio during the cycle of the secondary battery.

[0030] In one embodiment of the present application, 15≤D≤60. For example, D can be 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, or a range consisting of any two of the above values. By adjusting the value of D within the range of the present application, the secondary battery can have a higher energy density while taking into account better cycle performance.

[0031] In one embodiment of the present application, the sulfur-oxygen double bond compound includes 1,3-propane sultone, vinyl sulfate, propene sultone, 3-fluoro-1,3-propane sultone, 1,2-propane sultone, 1,4-butane sultone, 2,4-butane sultone or At least one of (Chinese name: 3a,6a-dihydro-2,5-disulfide-[1,3,2]dioxathiacyclopentane-[4,5-d][1,3,2]dioxathiacyclopentane-2,2,5,5-tetraketone). By selecting the above sulfur-oxygen double bond compound, a relatively stable positive electrode electrolyte interface film can be formed on the surface of the positive electrode material layer, thereby improving the problem of abnormal charge and discharge capacity ratio during the cycle of the secondary battery.

[0032] In one embodiment of the present application, the nitrile compound includes at least one of malononitrile, succinonitrile, glutaronitrile, adiponitrile, heptane dinitrile, octanedinitrile, 3,3'-oxydipropionitrile, hexamethylene dinitrile, trans-butene dinitrile, 2-pentene dinitrile, methyl glutaronitrile, 4-cyano heptane dinitrile, (Z)-butane-2-ene dinitrile, 2,2,3,3-tetrafluorosuccinonitrile, ethylene glycol bis (propionitrile) ether, 1,3,6-hexane trinitrile, 1,3,5-pentane tricarbonitrile, 4-(2-cyanoethyl) heptane dinitrile or 1,2,3-tris (2-cyanoethoxy) propane. By selecting the above-mentioned nitrile compounds, the nitrile compounds can be adsorbed on the positive electrode surface to cover the positive electrode active sites, reduce the side reactions of the positive electrode side electrolyte and the positive electrode material layer, thereby improving the problem of abnormal charge and discharge capacity ratio during the cycle of the secondary battery.

[0033] In one embodiment of the present application, the sulfur-oxygen double bond compound includes at least one of 1,3-propane sultone or vinyl sulfate, and the electrolyte also includes adiponitrile, succinonitrile and 1,3,6-hexanetrinitrile. The electrolyte includes the above compounds, which is more conducive to forming a relatively stable positive electrode electrolyte interface film on the surface of the positive electrode material layer and adsorbing on the positive electrode surface to cover the positive electrode active sites, reducing the side reactions of the electrolyte and the positive electrode material layer on the positive electrode side, thereby further improving the problem of abnormal charge and discharge capacity ratio during the cycle of the secondary battery.

[0034] In one embodiment of the present application, the sulfur-oxygen double bond compound includes at least one of 1,3-propane sultone or vinyl sulfate, and the electrolyte also includes adiponitrile and ethylene glycol bis(propionitrile) ether. The electrolyte includes the above compounds, which is more conducive to forming a relatively stable positive electrode electrolyte interface film on the surface of the positive electrode material layer and adsorbing on the positive electrode surface to cover the positive electrode active sites, reducing the side reactions of the electrolyte and the positive electrode material layer on the positive electrode side, thereby further improving the problem of abnormal charge and discharge capacity ratio during the cycle of the secondary battery.

[0035] In one embodiment of the present application, the electrolyte further comprises fluoroethylene carbonate (FEC), and the mass percentage of fluoroethylene carbonate is A3% based on the total mass of the electrolyte, 1.8≤A3≤9.8. Exemplarily, A3 can be 1.8, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5, 9.8 or a range consisting of any two of the above values. The electrolyte comprises FEC and the mass percentage of FEC is regulated within the scope of the present application, and FEC can form a relatively stable solid electrolyte interface film on the surface of the negative electrode material layer, reduce the generation of negative electrode side reaction products, and the synergistic protection of the positive electrode and the negative electrode can reduce the shuttle process of the positive electrode side reaction products to the negative electrode and the shuttle process of the negative electrode side reaction products to the positive electrode, thereby improving the problem of abnormal charge and discharge capacity ratio during the cycle of the secondary battery.

[0036] In one embodiment of the present application, 0.5≤A / A3≤5.2. Exemplarily, A / A3 can be 0.5, 0.7, 1, 1.3, 1.5, 1.7, 2, 2.3, 2.5, 2.7, 3, 3.3, 3.5, 3.7, 4, 4.3, 4.5, 4.7, 5, 5.2 or a range consisting of any two of the above values. By regulating the value of A / A3 within the scope of the present application, it is helpful to form a relatively complete positive electrode electrolyte interface film with a suitable thickness on the surface of the positive electrode material layer, and at the same time form a relatively complete solid electrolyte interface film with a suitable thickness on the surface of the negative electrode material layer, thereby improving the problem of abnormal charge and discharge capacity ratio during the cycle of the secondary battery.

[0037] In one embodiment of the present application, the electrolyte further comprises a compound of formula (I):

[0038]

[0039] wherein X is selected from CR6 or N; R1, R2 and R3 are each independently selected from a hydrogen atom, a halogen, a C2-C5 carbonyl group, a C1-C5 aldehyde group, a C1-C5 alkyl group which is unsubstituted or substituted by Ra, a C2-C5 alkenyl group which is unsubstituted or substituted by Ra, a C2-C5 alkynyl group which is unsubstituted or substituted by Ra, a C3-C5 N-heterocycloalkyl group which is unsubstituted or substituted by Ra, or a C3-C5 N-heteroaryl group; R4, R R5 and R6 are independently selected from hydrogen atom, C1-C5 alkylthio, C2-C5 thioether, C3-C5 N-heterocycloalkyl, C3-C5 N-heteroaryl, C1-C5 alkyl unsubstituted or substituted by Ra, C2-C5 alkenyl unsubstituted or substituted by Ra, C2-C5 alkynyl unsubstituted or substituted by Ra; wherein C1-C5 alkylthio is RS-, R is C1-C5 alkyl. The substituent Ra of each group is independently selected from halogen, C1-C5 aldehyde, C2-C5 carbonyl, C2-C5 ester, sulfonic acid, amino, C2-C5 amide or cyano.

[0040] In one embodiment of the present application, R1, R2 and R3 are each independently selected from a hydrogen atom, a fluorine atom, a chlorine atom, a bromine atom, an iodine atom, a formaldehyde group, an acetaldehyde group, an ethylcarbonyl group, a propylcarbonyl group, a methyl group, an ethyl group, a propyl group, a butyl group, a vinyl group, a propenyl group, a butenyl group, an ethynyl group, a propynyl group, a butynyl group, a pyrrolyl group or a pyridyl group; R4, R5 and R6 are each independently selected from a hydrogen atom, a methylsulfide group, a dimethylsulfide group, a methyl group, an ethyl, a propyl group, a butyl group, a vinyl group, a propenyl group, a butenyl group, an ethynyl group, a propynyl group, a butynyl group, a pyrrolyl group or a pyridyl group.

[0041] In one embodiment of the present application, based on the total mass of the electrolyte, the mass percentage of the compound of formula (I) is A4%, 0.01≤A4≤5, preferably 0.1≤A4≤3. Exemplarily, A4 can be 0.01, 0.05, 0.1, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5 or a range consisting of any two of the above values. By regulating the electrolyte to also include the compound of formula (I), the type and content of the compound of formula (I) within the scope of the present application, it is helpful to form a positive electrode electrolyte interface film with good ion diffusion performance and relatively stable on the surface of the positive electrode material layer, thereby improving the problem of abnormal charge and discharge capacity ratio during the cycle of the secondary battery.

[0042] In one embodiment of the present application, the compound of formula (I) is selected from at least one of the following compounds:

[0043]

[0044]

[0045] By selecting the compound of formula (I), a relatively stable positive electrode electrolyte interface film with good ion diffusion performance can be formed on the surface of the positive electrode material layer, thereby improving the problem of abnormal charge and discharge capacity ratio during the cycle of the secondary battery.

[0046] In one embodiment of the present application, the positive electrode material layer includes a positive electrode active material, the particle size Dv10 of the positive electrode active material is D1 μm, the particle size Dv50 of the positive electrode active material is D2 μm, 2.4≤D1≤5.5, and illustratively, D1 can be 2.4, 2.6, 2.8, 3, 3.2, 3.4, 3.6, 3.8, 4, 4.2, 4.4, 4.6, 4.8, 5, 5.2, 5.4, 5.5 or a range consisting of any two of the above values; 1.5≤D2 / D1≤5, and illustratively, D2 / D1 can be 1.5, 1.7, 1.9, 2, 2.3, 2.5, 2.7, 2.9, 3, 3.3, 3.5, 3.7, 3.9, 4, 4.3, 4.5, 4.7, 4.9, 5 or a range consisting of any two of the above values. By regulating the values ​​of D1 and D2 / D1 within the scope of this application, the positive electrode active material can have a suitable particle size, the side reactions of the electrolyte and the positive electrode material layer on the positive electrode side can be reduced, thereby reducing the generation of side reaction products on the positive electrode side, thereby improving the problem of abnormal charge and discharge capacity ratio during the cycle of the secondary battery.

[0047] In the present application, the particle size Dv50 of the positive electrode active material is D2μm, 3.6≤D2≤27.5. Exemplarily, D2 can be 3.6, 5, 8, 10, 12, 15, 20, 22, 25, 27.5 or a range consisting of any two of the above values. By regulating the value of D2 within the scope of the present application, the positive electrode active material can have a suitable particle size, and the side reactions of the positive electrode side electrolyte and the positive electrode material layer can be reduced, thereby reducing the generation of side reaction products on the positive electrode side, thereby improving the problem of abnormal charge and discharge capacity ratio during the cycle of the secondary battery.

[0048] In one embodiment of the present application, 4.8≤A×(D2 / D1)≤55, preferably 10≤A×(D2 / D1)≤50. Exemplarily, A×(D2 / D1) can be 4.8, 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55 or a range consisting of any two of the above values. By regulating the value of A×(D2 / D1) within the scope of the present application, the sum of the mass percentages of the sulfur-oxygen double bond compound and the nitrile compound matches the particle size of the positive electrode active material, and the two work synergistically to reduce the side reactions of the electrolyte and the positive electrode material layer on the positive electrode side, and reduce the generation of side reaction products on the positive electrode side, thereby improving the problem of abnormal charge and discharge capacity ratio during the cycle of the secondary battery.

[0049] In one embodiment of the present application, the average sphericity of the positive electrode active material is S50, 0.65≤S50≤0.99. Exemplarily, S50 can be 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 0.99 or a range consisting of any two of the above values. By regulating the value of S50 within the scope of the present application, it is helpful to reduce the pressure between the positive electrode active material particles in the positive electrode material layer during cold pressing, reduce the degree of crushing of the positive electrode active material particles, reduce the occurrence of side reactions of the positive electrode side electrolyte and the positive electrode material layer, and reduce the production of side reaction products on the positive electrode side, thereby improving the problem of abnormal charge and discharge capacity ratio during the cycle of the secondary battery.

[0050] The present application has no particular restrictions on the method of regulating the Dv10 and Dv50 of the positive electrode active material, as long as the purpose of the present application can be achieved. Exemplarily, the Dv10 and Dv50 of the positive electrode active material can be regulated by grinding the positive electrode active material. For example, the Dv10 and Dv50 of the positive electrode active material can be regulated by regulating the grinding time. Exemplarily, when other conditions remain unchanged, the Dv10 of the positive electrode active material decreases when the grinding time is extended, and the Dv50 of the positive electrode active material decreases; the Dv10 of the positive electrode active material increases when the grinding time is shortened, and the Dv50 of the positive electrode active material increases.

[0051] The present application does not particularly limit the method for regulating the average sphericity of the positive electrode active material, as long as the purpose of the present application can be achieved. For example, the average sphericity of the positive electrode active material can be regulated by changing the ball milling time. The longer the ball milling time, the greater the sphericity. For example, the average sphericity increases when the ball milling time is extended, and the average sphericity decreases when the ball milling time is shortened.

[0052] In the present application, the electrolyte also includes a lithium salt. The lithium salt may include various lithium salts commonly used in the art, such as at least one of LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, Li2SiF6, lithium bis(oxalate borate) (LiBOB) or lithium difluoroborate. Based on the total mass of the electrolyte, the mass percentage A5 of the lithium salt is 8% to 15%. For example, A5 may be 8, 9, 10, 11, 12, 13, 14, 15 or a range consisting of any two of the above values.

[0053] In the present application, the electrolyte also includes a non-aqueous solvent. The present application has no particular restrictions on the non-aqueous solvent, as long as the purpose of the present application can be achieved, for example, it may include but is not limited to at least one of carbonate compounds, carboxylate compounds, ether compounds or other organic solvents. The above-mentioned carbonate compounds may include but are not limited to at least one of chain carbonate compounds, cyclic carbonate compounds or fluorocarbonate compounds. The above-mentioned chain carbonate compounds may include but are not limited to at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC) or ethyl methyl carbonate (EMC). The above-mentioned cyclic carbonate compounds may include but are not limited to at least one of ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC) or vinyl ethylene carbonate (VEC). The fluorinated carbonate compound may include, but is not limited to, at least one of fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, or trifluoromethylethylene carbonate. The carboxylate compound may include, but is not limited to, at least one of methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decalactone, valerolactone, or caprolactone. The above-mentioned ether compound may include but is not limited to at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, 1-ethoxy-1-methoxyethane, 2-methyltetrahydrofuran or tetrahydrofuran. The above-mentioned other organic solvents may include but are not limited to at least one of dimethyl sulfoxide, 1,2-dioxolane, cyclopentane, methyl cyclopentane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate or trioctyl phosphate. Based on the total mass of the electrolyte, the mass percentage content A6 of the non-aqueous solvent is 56% to 89%. For example, A6 can be 56, 60, 65, 69, 70, 75, 80, 85, 87, 88, 89 or a range composed of any two of the above values.

[0054] In one embodiment of the present application, the electrolyte may include a lithium salt, a non-aqueous solvent, a sulfur-oxygen double bond compound, and a nitrile compound. The mass percentages of the lithium salt, the sulfur-oxygen double bond compound, and the nitrile compound are as described above, and the mass percentage of the non-aqueous solvent is A6%, 70%≤A6≤89%. The secondary battery including the above electrolyte has good cycle performance.

[0055] In one embodiment of the present application, the electrolyte may include a lithium salt, a non-aqueous solvent, a sulfur-oxygen double bond compound, a nitrile compound, and fluoroethylene carbonate. The mass percentages of the lithium salt, the sulfur-oxygen double bond compound, the nitrile compound, and the fluoroethylene carbonate are as described above, and the mass percentage of the non-aqueous solvent is A6%, 69%≤A6≤87%. The secondary battery including the above electrolyte has good cycle performance.

[0056] In one embodiment of the present application, the electrolyte may include a lithium salt, a non-aqueous solvent, a sulfur-oxygen double bond compound, a nitrile compound, and a compound of formula (I). The mass percentages of the lithium salt, the sulfur-oxygen double bond compound, the nitrile compound, and the compound of formula (I) are as described above, and the mass percentage of the non-aqueous solvent is A6%, 65%≤A6≤88%. The secondary battery including the above electrolyte has good cycle performance.

[0057] In one embodiment of the present application, the electrolyte may include a lithium salt, a non-aqueous solvent, a sulfur-oxygen double bond compound, a nitrile compound, fluoroethylene carbonate, and a compound of formula (I). The mass percentages of the lithium salt, the sulfur-oxygen double bond compound, the nitrile compound, the fluoroethylene carbonate, and the compound of formula (I) are as described above, and the mass percentage of the non-aqueous solvent is A6%, 56%≤A6≤87%. The secondary battery including the above electrolyte has good cycle performance.

[0058] In the present application, the positive electrode plate includes a positive electrode current collector and a positive electrode material layer arranged on at least one surface of the positive electrode current collector. The above-mentioned "positive electrode material layer arranged on at least one surface of the positive electrode current collector" means that the positive electrode material layer can be arranged on one surface of the positive electrode current collector along its own thickness direction, or it can be arranged on two surfaces of the positive electrode current collector along its own thickness direction. It should be noted that the "surface" here can be the entire area of ​​the positive electrode current collector or a partial area of ​​the positive electrode current collector. This application has no special restrictions, as long as the purpose of this application can be achieved. This application has no special restrictions on the positive electrode current collector, as long as the purpose of this application can be achieved. For example, it can include aluminum foil, aluminum alloy foil or a composite current collector (such as an aluminum-carbon composite current collector).

[0059] The positive electrode material layer of the present application includes a positive electrode active material. The present application has no particular restrictions on the positive electrode active material, as long as the purpose of the present application can be achieved. For example, the positive electrode active material may include lithium nickel cobalt manganese oxide (such as common NCM811, NCM622, NCM523, NCM111), lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium-rich manganese-based materials, lithium cobalt oxide (LiCoO2), lithium manganese oxide, lithium iron manganese phosphate or lithium titanate. At least one of the positive electrode material layer also includes a conductive agent and a binder. The present application has no particular restrictions on the type of conductive agent, as long as the purpose of the present application can be achieved. For example, the conductive agent may include but is not limited to conductive carbon black (Super P), carbon nanotubes (CNTs), carbon fibers, flake graphite, graphene, metal materials or conductive polymers. At least one of the above-mentioned carbon nanotubes may include but is not limited to single-walled carbon nanotubes and / or multi-walled carbon nanotubes. The above-mentioned carbon fibers may include but are not limited to vapor-grown carbon fibers (VGCF) and / or nano-carbon fibers. The above-mentioned metal material may include but is not limited to metal powder and / or metal fiber. Specifically, the metal may include but is not limited to at least one of copper, nickel, aluminum or silver. The above-mentioned conductive polymer may include but is not limited to at least one of polyphenylene derivatives, polyaniline, polythiophene, polyacetylene or polypyrrole. The present application has no particular restrictions on the binder, as long as the purpose of the present application can be achieved. For example, the binder may include but is not limited to polyacrylate, polyimide, polyamide, polyamide-imide, polyvinylidene fluoride (PVDF), polystyrene butadiene copolymer (styrene-butadiene rubber), sodium alginate, polyvinyl alcohol, polytetrafluoroethylene, polyacrylonitrile, sodium carboxymethyl cellulose, potassium carboxymethyl cellulose, sodium hydroxymethyl cellulose or potassium hydroxymethyl cellulose. The present application has no particular restrictions on the mass ratio of the positive active material, conductive agent and binder in the positive electrode material layer. Those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved.

[0060] The present application has no particular limitation on the thickness of the positive electrode current collector, as long as the purpose of the present application can be achieved, for example, the thickness of the positive electrode current collector is 5 μm to 20 μm. The present application has no particular limitation on the thickness of the positive electrode sheet, as long as the purpose of the present application can be achieved, for example, the thickness of the positive electrode sheet is 15 μm to 500 μm.

[0061] Optionally, the positive electrode plate may further include a conductive layer, which is located between the positive electrode current collector and the positive electrode material layer. The present application has no particular restrictions on the composition of the conductive layer, which may be a conductive layer commonly used in the art. The conductive layer includes a conductive agent and a binder. The present application has no particular restrictions on the conductive agent and the binder in the conductive layer, which may be at least one of the above conductive agent and the above binder. The present application has no particular restrictions on the mass ratio of the conductive agent and the binder in the conductive layer, and those skilled in the art may select according to actual needs, as long as the purpose of the present application can be achieved.

[0062] In the present application, the negative electrode plate includes a negative electrode current collector and a negative electrode material layer arranged on at least one surface of the negative electrode current collector. The above-mentioned "negative electrode material layer arranged on at least one surface of the negative electrode current collector" means that the negative electrode material layer can be arranged on one surface of the negative electrode current collector along its own thickness direction, or it can be arranged on two surfaces of the negative electrode current collector along its own thickness direction. It should be noted that the "surface" here can be the entire area of ​​the negative electrode current collector or a partial area of ​​the negative electrode current collector. This application has no special restrictions, as long as the purpose of this application can be achieved. This application has no special restrictions on the negative electrode current collector, as long as the purpose of this application can be achieved. For example, it can include copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, foam nickel, foam copper or a composite current collector, etc.

[0063] The negative electrode material layer of the present application includes a negative electrode active material. The present application has no particular limitation on the negative electrode active material, as long as the purpose of the present application can be achieved. For example, the negative electrode active material may include natural graphite, artificial graphite, mesophase microcarbon beads (MCMB), hard carbon, soft carbon, silicon, silicon-carbon composite, SiO x (0.5<x<1.6), Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, spinel structure lithium titanate Li4Ti5O 12 , Li-Al alloy or metallic lithium, etc. The negative electrode material layer of the present application also includes a binder and a thickener. The present application has no special restrictions on the binder and thickener in the negative electrode material layer, as long as the purpose of the present application can be achieved. For example, the binder may be at least one of the above binders, and the thickener may include but is not limited to sodium carboxymethyl cellulose. The negative electrode material layer of the present application also includes a conductive agent. The present application has no special restrictions on the conductive agent in the negative electrode material layer, as long as the purpose of the present application can be achieved. For example, the conductive agent may be at least one of the above conductive agents. The present application has no special restrictions on the mass ratio of the negative electrode active material, the binder, and the thickener in the negative electrode material layer. Those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved.

[0064] The present application has no particular restrictions on the thickness of the negative electrode current collector, as long as the purpose of the present application can be achieved, for example, the thickness of the negative electrode current collector is 4 μm to 12 μm. The present application has no particular restrictions on the thickness of the negative electrode material layer, as long as the purpose of the present application can be achieved, for example, the thickness of the negative electrode material layer on one surface of the negative electrode current collector is 30 μm to 250 μm. The present application has no particular restrictions on the thickness of the negative electrode pole piece, as long as the purpose of the present application can be achieved, for example, the thickness of the negative electrode pole piece is 30 μm to 500 μm.

[0065] Optionally, the negative electrode plate may further include a conductive layer, which is located between the negative electrode current collector and the negative electrode material layer. The present application has no particular restrictions on the composition of the conductive layer, which may be a conductive layer commonly used in the art. The conductive layer includes a conductive agent and a binder. The present application has no particular restrictions on the conductive agent and the binder in the conductive layer, which may be at least one of the above conductive agent and the above binder. The present application has no particular restrictions on the mass ratio of the conductive agent and the binder in the conductive layer, and those skilled in the art may select according to actual needs, as long as the purpose of the present application can be achieved.

[0066] In the present application, the separator is used to separate the positive electrode plate and the negative electrode plate, prevent the internal short circuit of the secondary battery, allow the electrolyte ions to pass freely, and do not affect the electrochemical charge and discharge process. The present application has no special restrictions on the separator, as long as the purpose of the present application can be achieved. For example, the material of the separator may include but is not limited to polyethylene (PE), polypropylene (PP)-based polyolefins (PO), polyesters (for example, polyethylene terephthalate (PET) film), cellulose, polyimide (PI), polyamide (PA), spandex or aramid; the type of separator may include at least one of a woven membrane, a non-woven membrane, a microporous membrane, a composite membrane, a rolled membrane or a spun membrane.

[0067] In the present application, the diaphragm may include a substrate and a surface treatment layer. The substrate may be a non-woven fabric or a composite film having a porous structure, and the material of the substrate may include at least one of polyethylene, polypropylene, polyethylene terephthalate or polyimide. Optionally, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film may be used. Optionally, a surface treatment layer is provided on at least one surface of the substrate, and the surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by a mixed polymer and an inorganic substance. For example, the inorganic layer includes inorganic particles and a binder, and the present application has no particular restrictions on the above-mentioned inorganic particles, for example, it may include at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. The present application has no particular restrictions on the above-mentioned binder, for example, it may be at least one of the aforementioned binders. The polymer layer contains a polymer, and the material of the polymer includes at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyvinyl pyrrolidone, polyvinyl ether, polyvinylidene fluoride or poly(vinylidene fluoride-hexafluoropropylene).

[0068] The secondary battery of the present application also includes a packaging bag for containing a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte, as well as other components known in the art in the secondary battery, and the present application does not limit the above other components. The present application does not specifically limit the packaging bag, and it can be a packaging bag known in the art, as long as it can achieve the purpose of the present application.

[0069] In the present application, the secondary battery may include, but is not limited to, a lithium metal secondary battery, a lithium ion secondary battery (lithium ion battery), a lithium polymer secondary battery or a lithium ion polymer secondary battery, etc.

[0070] The preparation process of the secondary battery of the present application is well known to those skilled in the art, and the present application has no particular restrictions. For example, it may include but is not limited to the following steps: stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and winding, folding and other operations as needed to obtain an electrode assembly of a winding structure, placing the electrode assembly in a packaging bag, injecting the electrolyte into the packaging bag and sealing it to obtain a secondary battery; or, stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and then fixing the four corners of the entire stacked structure with tape to obtain an electrode assembly of a stacked structure, placing the electrode assembly in a packaging bag, injecting the electrolyte into the packaging bag and sealing it to obtain a secondary battery. In addition, overcurrent protection elements, guide plates, etc. may also be placed in the packaging bag as needed to prevent the pressure inside the secondary battery from rising and overcharging and discharging. Among them, the packaging bag is a packaging bag known in the art, and the present application does not limit this.

[0071] The second aspect of the present application provides an electronic device, which includes the secondary battery in any of the above embodiments. Therefore, the electronic device provided by the present application has good performance.

[0072] The present application does not particularly limit the type of electronic device, which can be any electronic device known in the prior art. In some embodiments, the electronic device can include but is not limited to a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD television, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.

[0073] Example

[0074] The following examples and comparative examples are given to more specifically describe the embodiments of the present application. Various tests and evaluations were performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are based on mass.

[0075] Test methods and equipment:

[0076] Particle size test:

[0077] The particle size Dv10 and Dv50 of the positive electrode active material were tested using a particle size analyzer (model: MasterSizer 2000). In the volume-based particle size distribution of the material, starting from the small particle size, the particle size reaching 10% of the volume accumulation is Dv10, and the particle size reaching 50% of the volume accumulation is Dv50.

[0078] Average sphericity test:

[0079] The images of 100 particles were captured and processed using a Malvern automatic image particle size analyzer (model: Morphologi 4-ID). The microstructure and morphology of the particles were then analyzed using image-guided Raman spectroscopy (MDRS). The longest diameter and shortest diameter of all particles were obtained, and the ratio of the shortest diameter to the longest diameter of each particle was calculated and averaged to obtain the average sphericity S50 of the particles.

[0080] Thickness test of positive electrode material layer:

[0081] The lithium-ion batteries of each embodiment and comparative example were discharged to 2.8V at a constant current of 0.5C and then disassembled, the positive electrode sheet was taken out, soaked in dimethyl carbonate (DMC) for 20 minutes, and then rinsed with DMC and acetone in turn. After that, the positive electrode sheet was placed in an oven and baked at 85°C for 12 hours to obtain a disassembled positive electrode sheet sample. An ion polisher (IB-09010CP) was used to polish the cross section along the thickness direction of the positive electrode sheet to obtain a cross-section of the positive electrode sheet, thereby preparing a sample for scanning electron microscopy testing. The thickness of the positive electrode material layer was tested by scanning electron microscopy, and the thickness of the positive electrode material layer at 5 different positions was randomly tested, and the average value was calculated to obtain the thickness D of the positive electrode material layer.

[0082] Test of the content of each component in the electrolyte:

[0083] The lithium-ion batteries of the embodiments and comparative examples were discharged to 2.8V at a constant current of 0.5C and then disassembled to collect the electrolyte. The positive electrode sheet, negative electrode sheet and diaphragm removed were centrifuged, and the liquid obtained after centrifugation was evenly mixed with the above electrolyte. Then, the components in the electrolyte were obtained and their contents were tested using a gas chromatography-mass spectrometer (instrument model: Agilent 8890) and an ion chromatography (instrument model: AQUION ion chromatography).

[0084] C / D test during the cycle:

[0085] At 45°C, discharge the lithium-ion battery to 3.0V at a constant current of 0.5C. After standing for 5 minutes, charge it to 4.25V at a constant current of 1.2C, charge it to 4.25V at a constant voltage of 4.25V until the current is 0.7C, then charge it to 4.5V at a constant current of 0.7C, charge it to 0.05C at a constant voltage of 4.5V. This is the first charge, and the charge capacity C0 of the first charge is recorded. After standing for 5 minutes, discharge it to 3.0V at a constant current of 0.5C. This is the first discharge, and the discharge capacity D0 of the first discharge is recorded. This completes a cycle. The lithium-ion battery is cycled 200 times under the above conditions, and the charge capacity, discharge capacity, and the ratio of charge capacity to discharge capacity C / D of each cycle are recorded. The maximum value of C / D in 200 cycles of the lithium-ion battery (C / D) is max As an indicator for evaluating the C / D of lithium-ion batteries.

[0086] The C / D value usually reflects the capacity loss and self-discharge during the cycle. Due to irreversible capacity loss, the C / D value is usually greater than 1. If there is a shuttle type or transition metal dendrite that triggers self-discharge, it will lead to an increase in charge capacity and a decrease in discharge capacity, thereby increasing the C / D ratio. (C / D) can be used max As a standard to determine whether there is an abnormal charge / discharge capacity ratio during the cycle of lithium-ion batteries, (C / D) max The closer it is to 1, the better the performance of the lithium-ion battery. (C / D) max ≤1.05, indicating a low risk of circulatory abnormalities; (C / D) max >1.05, indicating that the risk of abnormal charge-discharge capacity ratio is high.

[0087] Example 1-1

[0088] <Preparation of Electrolyte>

[0089] In an argon atmosphere glove box with a water content of less than 10ppm, EC, PC and DEC were mixed in a mass ratio of 10:30:60 to obtain a base solvent, and then lithium salt LiPF6, sulfur-oxygen double bond compound 1,3-propane sultone (1,3-PS) and nitrile compounds adiponitrile (ADN), succinonitrile (SN) and 1,3,6 hexane trinitrile (HTCN) were added to the base solvent, and stirred evenly to obtain an electrolyte. Among them, based on the total mass of the electrolyte, the mass percentage content A5 of LiPF6 is 12%, the mass percentage content A1 of the sulfur-oxygen double bond compound is 0.52%, the mass percentage content A2 of the nitrile compound is 6.5%, and the balance is the base solvent.

[0090] <Preparation of positive electrode sheet>

[0091] LiCoO2 was ball-milled for 12 h to obtain the positive electrode active material LiCoO2 with an average sphericity S50 of 0.9.

[0092] The positive electrode active material LiCoO2, the conductive agent conductive carbon black, and the binder PVDF are mixed in a mass ratio of 95:2:3, N-methylpyrrolidone (NMP) is added, and the mixture is stirred evenly under the action of a vacuum mixer to obtain a positive electrode slurry with a solid content of 70wt%. The positive electrode slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 9μm, and the aluminum foil is dried at 85°C for 4h to obtain a positive electrode sheet with a single-sided positive electrode material layer coated with a coating thickness of 110μm and a width of 74mm. Repeat the above steps on the other surface of the aluminum foil to obtain a positive electrode sheet with a double-sided positive electrode material layer coated. After cold pressing, cutting, and slitting, a positive electrode sheet with a specification of 74mm×867mm is obtained. Among them, the values ​​of D and A / D are shown in Table 1; the particle size Dv10 (ie, D1) of the positive electrode active material is 3, the particle size Dv50 (ie, D2) of the positive electrode active material is 12, D2 / D1 is 4, and A×(D2 / D1) is 28.4.

[0093] <Preparation of negative electrode sheet>

[0094] The negative electrode active material artificial graphite, the binder styrene-butadiene rubber, and the thickener sodium carboxymethyl cellulose are mixed in a mass ratio of 95:2:3, deionized water is added, and the mixture is stirred evenly under the action of a vacuum mixer to obtain a negative electrode slurry with a solid content of 75wt%. The negative electrode slurry is evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 12μm, and the copper foil is dried at 85°C for 4h to obtain a negative electrode sheet with a single-sided negative electrode material layer coated with a coating thickness of 130μm and a width of 76.6mm. Repeat the above steps on the other surface of the copper foil to obtain a negative electrode sheet with a double-sided negative electrode material layer coated. After cold pressing, cutting, and slitting, a negative electrode sheet with a specification of 76.6mm×875mm is obtained.

[0095] <Preparation of Separator>

[0096] The binder PVDF and the inorganic particle alumina were mixed in a mass ratio of 1:2, NMP was added as a solvent, and an inorganic layer slurry with a solid content of 12wt% was prepared. The inorganic layer slurry was evenly coated on one surface of a polyethylene substrate with a thickness of 5μm, and dried at 85℃ for 4h to obtain a diaphragm with a single-sided inorganic layer coated with a coating thickness of 2μm. Then PVDF was added to the NMP solvent and stirred evenly to prepare a polymer layer slurry with a solid content of 25wt%, and then the polymer layer slurry was evenly coated on the surface of the inorganic layer. The surface density of the coated polymer layer slurry was 0.15mg / cm 2 , and then dried at 85°C for 4 hours, and finally the other surface of the polyethylene substrate was evenly coated with a polymer layer slurry, and the surface density of the coated polymer layer slurry was 0.15 mg / cm 2 , and then dried at 85°C for 4 hours to obtain a diaphragm coated with an inorganic layer and a polymer layer on one side and only a polymer layer on the other side.

[0097] <Preparation of lithium-ion batteries>

[0098] The positive electrode sheet, separator, and negative electrode sheet prepared above are stacked in order, so that the side of the separator coated with the inorganic layer and the polymer layer faces the positive electrode sheet, and the side coated with only the polymer layer faces the negative electrode sheet, so that the separator is between the positive electrode sheet and the negative electrode sheet to play a role of isolation, and then wound to obtain an electrode assembly. After welding the pole ear, the electrode assembly is placed in an aluminum-plastic film packaging bag, placed in an 85°C vacuum oven for 12 hours to remove moisture, and the above-prepared electrolyte is injected. After vacuum packaging, standing, formation (0.02C constant current charging to 3.5V, and then 0.1C constant current charging to 3.9V), shaping and other processes, a lithium-ion battery is obtained.

[0099] Example 1-2 to Example 1-34

[0100] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as Example 1-1. When the mass percentage of the added sulfur-oxygen double bond compound and the nitrile compound changes, the mass percentage of the base solvent changes accordingly, and the mass ratio of EC, PC, DEC and the mass percentage of the lithium salt remain unchanged.

[0101] Example 2-1 to Example 2-8

[0102] Except for adding fluoroethylene carbonate as shown in Table 2 and adjusting relevant preparation parameters as shown in Table 2, the rest is the same as Example 1-6. Among them, when the mass percentage of the added fluoroethylene carbonate, the sulfur-oxygen double bond compound, and the nitrile compound changes, the mass percentage of the base solvent changes accordingly, and the mass ratio of EC, PC, DEC and the mass percentage of the lithium salt remain unchanged.

[0103] Example 3-1 to Example 3-11

[0104] Except for adding the compound of formula (I) as shown in Table 3 and adjusting the relevant preparation parameters according to Table 3, the rest is the same as Example 1-6. Among them, when the mass percentage of the added compound of formula (I), the sulfur-oxygen double bond compound, and the nitrile compound changes, the mass percentage of the base solvent changes accordingly, and the mass ratio of EC, PC, DEC and the mass percentage of the lithium salt remain unchanged.

[0105] Example 3-12

[0106] Except for adding fluoroethylene carbonate and the compound of formula (I) as shown in Table 3 and adjusting the relevant preparation parameters according to Table 3, the rest is the same as Example 1-6. After adding fluoroethylene carbonate and the compound of formula (I), the mass percentage of the base solvent changes accordingly, and the mass ratio of EC, PC, DEC and the mass percentage of lithium salt in the base solvent remain unchanged.

[0107] Example 4-1 to Example 4-10

[0108] Except for adjusting the relevant preparation parameters according to Table 4, the rest is the same as Example 3-12.

[0109] Example 4-11 to Example 4-13

[0110] Except that the ball milling time was adjusted so that the average sphericity S50 of the positive electrode active material was as shown in Table 4, the rest was the same as Example 3-12.

[0111] Comparative Example 1 to Comparative Example 11

[0112] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as Example 1-1.

[0113] The preparation parameters and electrical performance parameters of each embodiment and comparative example are shown in Tables 1 to 4.

[0114] Table 1

[0115]

[0116]

[0117]

[0118] Note: " / " in Table 1 indicates no relevant preparation parameters, compound S is

[0119] Referring to Table 1, it can be seen from Examples 1-1 to 1-34 and Comparative Examples 1 to 11 that the electrolyte includes a sulfur-oxygen double bond compound and a nitrile compound, and the mass ratio A1 / A2 of the sulfur-oxygen double bond compound and the nitrile compound and the mass sum A, the ratio A / D of the sum of the mass of the sulfur-oxygen double bond compound and the nitrile compound to the thickness of the positive electrode material layer are regulated within the scope of this application. The maximum value (C / D) of C / D in 200 cycles of the lithium ion battery is max The lower the charge / discharge capacity ratio, the better the problem of abnormal charge / discharge capacity ratio during the cycle of the secondary battery. In Comparative Examples 1 to 11, the maximum value of C / D (C / D) of the lithium-ion battery in 200 cycles is max It is higher, indicating that there is an abnormal charge and discharge capacity ratio problem during the cycle of the lithium-ion battery.

[0120] The mass percentage content A1 of the sulfur-oxygen double bond compound and the mass percentage content A2 of the nitrile compound will also generally affect the charge-discharge capacity ratio during the cycle of the lithium-ion battery. From Examples 1-1 to 1-14 and 1-26 to 1-30, it can be seen that by adjusting the values ​​of A1 and A2 within the scope of this application, the maximum value (C / D) of the C / D of the lithium-ion battery in 200 cycles is max It is relatively low, indicating that the problem of abnormal charge and discharge capacity ratio during the cycle of lithium-ion batteries can be improved.

[0121] The thickness D of the positive electrode material layer usually affects the cycle performance and energy density of the lithium-ion battery. It can be seen from Examples 1-1, 1-15 to 1-16, and 1-24 to 1-25 that by adjusting the value of D within the scope of this application, the maximum value of C / D (C / D) of the lithium-ion battery in 200 cycles is max It is lower, indicating that the cycle performance of lithium-ion batteries is better.

[0122] The type of sulfur-oxygen double bond compound usually also affects the charge-discharge capacity ratio during the cycle of the lithium-ion battery. From Examples 1-10, 1-17 to 1-19, and 1-31, it can be seen that by adjusting the type of sulfur-oxygen double bond compound within the scope of this application, the maximum C / D value (C / D) of the lithium-ion battery in 200 cycles is max It is relatively low, indicating that the problem of abnormal charge and discharge capacity ratio during the cycle of lithium-ion batteries can be improved.

[0123] The type of nitrile compound usually also affects the charge-discharge capacity ratio during the cycle of the lithium-ion battery. It can be seen from Examples 1-10, 1-20 to 1-22, and 1-32 to 1-34 that by adjusting the type of nitrile compound within the scope of this application, the maximum value of C / D (C / D) of the lithium-ion battery in 200 cycles is max It is relatively low, indicating that the problem of abnormal charge and discharge capacity ratio during the cycle of lithium-ion batteries can be improved.

[0124] Table 2

[0125] A1(%) A2(%) A(%) A3(%) A / A3 <![CDATA[(C / D) max ]]> Examples 1-6 4 6 10 / / 1.013 Example 2-1 3 6 9 1.8 5 1.011 Example 2-2 4 6 10 5 2 1.01 Example 2-3 4 6 10 9.8 1.02 1.008 Embodiment 2-4 1 3 4 8 0.5 1.009 Embodiment 2-5 3.5 6.5 10 4 2.5 1.007 Embodiment 2-6 5 8 13 2.5 5.2 1.008 Embodiment 2-7 0.6 2.4 3 7.5 0.4 1.011 Embodiment 2-8 5 10 15 2.5 6 1.012

[0126] Note: “ / ” in Table 2 indicates no relevant preparation parameters.

[0127] The electrolyte also includes fluoroethylene carbonate and the mass percentage of fluoroethylene carbonate A3 will usually affect the charge-discharge capacity ratio during the cycle of the lithium-ion battery. From Examples 1-6, 2-1 to 2-3, it can be seen that by adjusting the values ​​of the electrolyte also including fluoroethylene carbonate and A3 within the scope of this application, the maximum value of C / D (C / D) of the lithium-ion battery in 200 cycles is max It is relatively low, indicating that the problem of abnormal charge and discharge capacity ratio during the cycle of lithium-ion batteries can be improved.

[0128] A / A3 also usually affects the charge-discharge capacity ratio of the lithium-ion battery during the cycle. It can be seen from Examples 1-6 and 2-1 to 2-8 that by adjusting the value of A / A3 within the scope of this application, the maximum value of C / D (C / D) of the lithium-ion battery in 200 cycles is max It is relatively low, indicating that the problem of abnormal charge and discharge capacity ratio during the cycle of lithium-ion batteries can be improved.

[0129] Table 3

[0130] Compound of formula (I) A4(%) A3(%) A / A3 <![CDATA[(C / D) max ]]> Examples 1-6 / / / / 1.013 Example 3-1 Formula (I-1) 0.5 / / 1.011 Example 3-2 Formula (I-4) 0.5 / / 1.01 Example 3-3 Formula (I-7) 0.5 / / 1.008 Embodiment 3-4 Formula (I-8) 0.5 / / 1.01 Embodiment 3-5 Formula (I-9) 0.5 / / 1.011 Embodiment 3-6 Formula (I-11) 0.5 / / 1.009 Embodiment 3-7 Formula (I-7) 0.01 / / 1.012 Embodiment 3-8 Formula (I-7) 2.5 / / 1.009 Embodiment 3-9 Formula (I-7) 5 / / 1.012 Embodiment 3-10 Formula (I-7) 0.1 / / 1.011 Example 3-11 Formula (I-7) 3 / / 1.010 Example 3-12 Formula (I-7) 0.5 5 2 1.006

[0131] Note: “ / ” in Table 3 indicates no relevant preparation parameters.

[0132] The electrolyte also includes the compound of formula (I) and the mass percentage of the compound of formula (I) A4, which usually also affects the charge-discharge capacity ratio during the cycle of the lithium-ion battery. It can be seen from Examples 1-6, 3-7 to 3-11 that by adjusting the values ​​of the compound of formula (I) and A4 in the electrolyte within the scope of this application, the maximum value of C / D (C / D) of the lithium-ion battery in 200 cycles is max It is relatively low, indicating that the problem of abnormal charge and discharge capacity ratio during the cycle of lithium-ion batteries can be improved.

[0133] The type of compound of formula (I) will generally affect the charge-discharge capacity ratio during the cycle of the lithium-ion battery. It can be seen from Examples 1-6 and Examples 3-1 to 3-6 that by adjusting the type of compound of formula (I) within the scope of this application, the maximum value of C / D (C / D) of the lithium-ion battery in 200 cycles is max It is relatively low, indicating that the problem of abnormal charge and discharge capacity ratio during the cycle of lithium-ion batteries can be improved.

[0134] It can be seen from Examples 3-12 that the electrolyte includes fluoroethylene carbonate and the compound of formula (I), and the maximum C / D value (C / D) of the lithium ion battery in 200 cycles is max It is lower, which means that the problem of abnormal charge and discharge capacity ratio during the cycle of lithium-ion batteries can be better improved.

[0135] Table 4

[0136]

[0137]

[0138] The ratio of the particle size Dv10 (i.e., D1) of the positive electrode active material and the particle size Dv50 (i.e., D2) of the positive electrode active material to the particle size Dv10 of the positive electrode active material will generally also affect the charge-discharge capacity ratio during the cycle of the lithium-ion battery. It can be seen from Examples 3-12 and 4-1 to 4-6 that by adjusting the values ​​of D1 and D2 / D1 within the scope of this application, the maximum value (C / D) of C / D in 200 cycles of the lithium-ion battery is max It is relatively low, indicating that the problem of abnormal charge and discharge capacity ratio during the cycle of lithium-ion batteries can be improved.

[0139] The value of A×(D2 / D1) will also affect the charge / discharge capacity ratio of the lithium-ion battery during the cycle. It can be seen from Examples 3-12, 4-1 to 4-10 that by adjusting the value of A×(D2 / D1) within the scope of this application, the maximum value of C / D (C / D) of the lithium-ion battery in 200 cycles is max It is relatively low, indicating that the problem of abnormal charge and discharge capacity ratio during the cycle of lithium-ion batteries can be improved.

[0140] The average sphericity S50 of the positive electrode active material usually also affects the charge-discharge capacity ratio during the cycle of the lithium-ion battery. It can be seen from Examples 3-12, 4-11 and 4-13 that by adjusting the value of S50 within the scope of this application, the maximum C / D value (C / D) of the lithium-ion battery in 200 cycles is max It is relatively low, indicating that the problem of abnormal charge and discharge capacity ratio during the cycle of lithium-ion batteries can be improved.

[0141] It should be noted that the terms "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method or article that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method or article.

[0142] Each embodiment in this specification is described in a related manner, and the same or similar parts between the embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.

[0143] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.

Claims

1. A secondary battery, comprising a positive electrode plate, a negative electrode plate, a separator and an electrolyte, wherein the electrolyte comprises a sulfur-oxygen double bond compound and a nitrile compound, based on the total mass of the electrolyte, the mass percentage of the sulfur-oxygen double bond compound is A1%, the mass percentage of the nitrile compound is A2%, 0.08≤A1 / A2≤2.15; the sum of the mass percentages of the sulfur-oxygen double bond compound and the nitrile compound is A%, 3≤A≤15; The positive electrode plate includes a positive electrode current collector and a positive electrode material layer disposed on at least one surface of the positive electrode current collector. The thickness of the positive electrode material layer is D μm, and 0.08≤A / D≤0.

42.

2. The secondary battery according to claim 1, wherein The secondary battery satisfies at least one of the following characteristics: (1) 0.142≤A / D≤0.42; (2) 0.5≤A1≤5.2, 2.4≤A2≤8.1; (3)15≤D≤60。 3. The secondary battery according to claim 1, wherein The sulfur-oxygen double bond compound includes 1,3-propane sultone, vinyl sulfate, propylene sultone, 3-fluoro-1,3-propane sultone, 1,2-propane sultone, 1,4-butane sultone, 2,4-butane sultone or at least one of; The nitrile compound includes at least one of malononitrile, succinonitrile, glutaronitrile, adiponitrile, heptane dinitrile, suberonitrile, 3,3'-oxydipropionitrile, hexane-2-enedinitrile, butene dinitrile, 2-pentene dinitrile, methyl glutaronitrile, 4-cyanopeptane dinitrile, (Z)-but-2-enedinitrile, 2,2,3,3-tetrafluorosuccinonitrile, ethylene glycol bis(propionitrile) ether, 1,3,6-hexanetrinitrile, 1,3,5-pentanetricarbonitrile, 4-(2-cyanoethyl)heptane dinitrile or 1,2,3-tris(2-cyanoethoxy)propane.

4. The secondary battery according to claim 1, wherein The electrolyte satisfies at least one of the following characteristics: (1) The sulfur-oxygen double bond compound includes at least one of 1,3-propane sultone or vinyl sulfate, and the electrolyte further includes adiponitrile, succinonitrile and 1,3,6-hexanetrinitrile; (2) The sulfur-oxygen double bond compound includes at least one of 1,3-propane sultone or vinyl sulfate, and the electrolyte further includes adiponitrile and ethylene glycol bis(propionitrile) ether.

5. The secondary battery according to claim 1, wherein The electrolyte further comprises fluoroethylene carbonate, and based on the total mass of the electrolyte, the mass percentage of the fluoroethylene carbonate is A3%, 1.8≤A3≤9.

8.

6. The secondary battery according to claim 5, wherein 0.5≤A / A3≤5.

2.

7. The secondary battery according to claim 1, wherein The electrolyte also includes a compound of formula (I): wherein X is selected from CR6 or N; R1, R2 and R3 are each independently selected from a hydrogen atom, a halogen, a C2-C5 carbonyl group, a C1-C5 aldehyde group, a C1-C5 alkyl group which is unsubstituted or substituted by Ra, a C2-C5 alkenyl group which is unsubstituted or substituted by Ra, a C2-C5 alkynyl group which is unsubstituted or substituted by Ra, a C3-C5 N-heterocycloalkyl group which is unsubstituted or substituted by Ra, a C3-C5 N-heteroaryl group; R4, R5 and R6 are each independently selected from a hydrogen atom, a C1-C5 alkylthio group, a C2-C5 thioether, a C3-C5 N-heterocycloalkyl group, a C3-C5 N-heteroaryl group, a C1-C5 alkyl group which is unsubstituted or substituted by Ra, a C2-C5 alkenyl group which is unsubstituted or substituted by Ra, and a C2-C5 alkynyl group which is unsubstituted or substituted by Ra; The substituents Ra of each group are independently selected from halogen, C1-C5 aldehyde group, C2-C5 carbonyl group, C2-C5 ester group, sulfonic acid group, amino group, C2-C5 amide group or cyano group; Based on the total mass of the electrolyte, the mass percentage of the compound of formula (I) is A4%, 0.01≤A4≤5, preferably 0.1≤A4≤3.

8. The secondary battery according to claim 7, wherein The compound of formula (I) is selected from at least one of the following compounds:

9. The secondary battery according to claim 1, wherein The positive electrode material layer includes a positive electrode active material, the particle size Dv10 of the positive electrode active material is D1 μm, the particle size Dv50 of the positive electrode active material is D2 μm, 2.4≤D1≤5.5, and 1.5≤D2 / D1≤5.

10. The secondary battery according to claim 9, wherein 4.8≤A×(D2 / D1)≤55, preferably 10≤A×(D2 / D1)≤50.

11. The secondary battery according to claim 9, wherein The average sphericity of the positive electrode active material is S50, 0.65≤S50≤0.

99. 12 . An electronic device comprising the secondary battery according to claim 1 .